Adolescent female body image: self-report predictive cognitions and behaviors - Wearing Lancaster, Sarah (Kansas State University, 2018)
Adolescence is a time when many experience challenges in life to which they have not been previously exposed. Complicating the transition to adolescence is the perception that they are “on stage” and everyone is watching and evaluating their transition through puberty (Woolfolk, 2019). Youth face the challenge of separating themselves from their parents, gaining more independence, and growing into their own identity (Erikson, 1968; Woolfolk, 2019). With this independence arises more reliance on peers, friends, and outside influences. They are faced with decisions to make about their postsecondary choice, career path, goal setting, body image issues, identity, sexual selves, and peer relationships. Gender differences in self-esteem have also been shown to emerge during adolescence, with girls displaying lower levels of self-esteem than their male peers (Impett, Sorsoli, Schooler, Henson, & Tolman, 2008). The emphasis on fitness, thinness, and outward beauty, increases the pressure on adolescents, specifically for this study, females to have the “perfect” body to fit with society ideals (Hartocollis, 2013). The study explored self-esteem, self-efficacy, life satisfaction, social comparison, and body image in 8th and 12th grade girls from a rural middle school and a rural high school in a mid-size Midwestern city. The study population included 97 participants among the two schools and utilized a cross-sectional design, causal-comparative. Survey results indicated 12th grade girls do not have higher self-esteem, life satisfaction, or self-efficacy and reported lower “how I look” and “how I feel” body image than 8th grade girls. However, 12th grade girls reported engaging in social comparison less than 8th grade girls. It is significant that girls in the study who reported school-based curriculum exposure to nutrition, goal setting, and respecting their sexual selves reported higher life satisfaction, self-esteem, and self-efficacy. The girls also reported engaging in less social comparison. The results from this study indicated the need and strong support for intentional school-based curricula. Self-esteem, self-efficacy, body image and social comparison are factors in life satisfaction and should be addressed as part of a comprehensive, standards based social-emotional curriculum.
Keywords: Self-esteem; Self-efficacy; Body image; Life satisfaction; Social comparison; Female adolescents